Genetic diversity and geographical distribution of strains of mycobacterium tuberculosis complex in Ethiopia: Review - Mitiku wamile Arada (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
In Ethiopia, tuberculosis (TB) is one of the major infectious diseases with wide spread geographic distribution and endemic nature, which has been well documented both in human and livestock of the country. TB in livestock has an important economic and public health significance although the actual prevalence of animal tuberculosis at the national level is yet unknown. Identification of the etiology of tuberculosis in human and different species of livestock has a paramount significance in order to understand the transmission pattern, the pathogenesis, and control of the diseases. So far, detection of animal TB in Ethiopia has been carried out most commonly on the basis of tuberculin skin testing, abattoir meat inspection and very rarely on bacteriological techniques. These diagnostic methods can not differentiate the specific species of Mycobacterium tuberculosis complex or other species /strains of Mycobacterium, hence utilization of advanced molecular techniques to characterize and genotype the causative agents is important. Genotyping of Mycobaterium species allows understanding the genetic diversity, transmission dynamics and evolutionary/phylogenic  relationships of the isolates in different hosts of animal and human. The aim of this paper is, therefore, to review molecular genetic diversity and distribution of mycobacterial infection due to M.tuberculosis complex (mainly M.bovis, M.tuberculosis) and non-tuberculous mycobacterium in Ethiopia in addition to highlighting the zoonotic significance of mycobacterial species originated from livestock and to show the feasible prevention and control options of tuberculosis in cattle and other animals.